2023
DOI: 10.1111/1365-2745.14093
|View full text |Cite
|
Sign up to set email alerts
|

Airborne laser scanning reveals uniform responses of forest structure to moose (Alces alces) across the boreal forest biome

Abstract: The moose Alces alces is the largest herbivore in the boreal forest biome, where it can have dramatic impacts on ecosystem structure and dynamics. Despite the importance of the boreal forest biome in global carbon cycling, the impacts of moose have only been studied in disparate regional exclosure experiments, leading to calls for common analyses across a biome‐wide network of moose exclosures. In this study, we use airborne laser scanning (ALS) to analyse forest canopy responses to moose across 100 paired exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…To start, these networks could be an accumulation of existing experiments. For example, Petersen et al (2023) assembled data from 100 paired moose exclosure-control plots across five countries and a large primary productivity gradient to demonstrate consistent responses of forest structure to moose exclusion. Conducting a similar analysis of soil responses across exclosure experiments would let us make more general conclusions below-ground.…”
Section: Discussionmentioning
confidence: 99%
“…To start, these networks could be an accumulation of existing experiments. For example, Petersen et al (2023) assembled data from 100 paired moose exclosure-control plots across five countries and a large primary productivity gradient to demonstrate consistent responses of forest structure to moose exclusion. Conducting a similar analysis of soil responses across exclosure experiments would let us make more general conclusions below-ground.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative viewshed provided by the 3D LiDAR beams revealed not only the level of preferred visibility, but also a significant difference between preferred visibilities during day and night/twilight. A related study by Petersen et al (2023) showed how metrics extracted from airborne LiDAR‐related fine‐scale forest structure to moose Alces alces in a boreal biome and helped test the hypothesis that biomass, canopy height and vertical complexity were all negatively correlated with the presence of moose. The thorough analysis additionally comprised examining whether the impacts vary with a set of climatic and disturbance‐related factors and suggested largely uniform responses across multiple test sites distributed over the boreal biome.…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
“…3. At the interface of forest structure and wildlife monitoring (Davison et al, 2023;Lee et al, 2023;Petersen et al, 2023;Yoh et al, 2023;Zong et al, 2022).…”
Section: Climate-mediated Response Of Animal Populations (From Insectsmentioning
confidence: 99%
See 1 more Smart Citation